Comparing effectiveness and safety of combination therapy for esophageal and gastro esophageal junction cancer: a comprehensive meta-analysis - Abir, Shifaty Nur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.